Effect of disinfection and tissue repair with chloramphenicol-tetracycline-ZOE paste on pulp therapy of primary teeth: a systematic review - Souza, José Antonio Santos [UNESP]; de Oliveira Alves, Renata [UNESP]; de Toledo, Priscila Toninatto Alves; Mota, Heloisa Caroline [UNESP]; Martins, Tamires Passadori [UNESP]; Danelon, Marcelle; Duque, Cristiane; Nunes, Gabriel Pereira (Springer Nature, 2025)
ObjectiveThis systematic review evaluated the effectiveness of the disinfection and tissue repair technique using chloramphenicol-tetracycline-zinc oxide eugenol paste (CTZ) in pulp therapy of primary teeth.MethodsFollowing PRISMA 2020 guidelines and PROSPERO registration, comprehensive searches were conducted in multiple databases. Eligibility criteria included clinical studies evaluating CTZ paste in children with pulp necrosis in primary teeth. Risk of bias was assessed using the Cochrane tool for randomized trials and the Newcastle-Ottawa Scale for non-randomized studies. Certainty of evidence was assessed using GRADE.ResultsTen studies, including 496 children aged 3–8 years, met the inclusion criteria. CTZ paste showed high clinical success rates (~ 90–100%) and radiographic success ranging from 72% to 100%. Compared to alternative treatments such as zinc oxide eugenol, 3Mix-MP, formocresol, Guedes-Pinto paste, and pulpectomy, CTZ showed similar outcomes in most comparisons. Additional advantages included reduced postoperative pain, simpler application, and lower procedural costs, suggesting its practicality in pediatric endodontics. Overall, studies presented a low risk of bias. Certainty of evidence was rated moderate for randomized trials and low for non-randomized studies.ConclusionCTZ paste demonstrates potential as an effective and cost-efficient therapeutic option for the treatment of necrotic primary teeth, showing high clinical and radiographic success rates. Further well-designed, long-term randomized controlled trials are needed to confirm these findings.Clinical relevanceCTZ paste offers simplified, cost-effectiveness, and high success rates make it valuable in pediatric dentistry, especially for uncooperative children and in low-resource settings where conventional endodontic techniques may be unfeasible.